1999
DOI: 10.2134/agronj1999.916946x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Comparisons among Different Maize Maturity Rating Systems

Abstract: Several systems are extensively used to rate maize (Zea mays L.) maturity in North America, including growing degree days, crop heat units, and Minnesota relative maturity rating days. Correspondence between the different systems varies with the temperature range of the environment, because of different bases of calculation and unit size. However, general guidelines for conversion from one system to another would aid communication among researchers, producers, distributors, and extension personnel, particularl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 6 publications
0
41
0
2
Order By: Relevance
“…We found that population densities of 100 000 plants ha -1 or greater often were required to maximize whole-plant yield with these earlier-maturing hybrids under Alberta con- Irrigation water applied (mm) 330 225 z Accumulated corn heat units according to Dwyer et al (1999). y Long-term averages were determined from the years 1972 to 2002.…”
Section: Resultsmentioning
confidence: 99%
“…We found that population densities of 100 000 plants ha -1 or greater often were required to maximize whole-plant yield with these earlier-maturing hybrids under Alberta con- Irrigation water applied (mm) 330 225 z Accumulated corn heat units according to Dwyer et al (1999). y Long-term averages were determined from the years 1972 to 2002.…”
Section: Resultsmentioning
confidence: 99%
“…Soil moisture was never limiting at either location. To relate CHU accumulation to other thermal unit maturity rating systems see Dwyer et al (1999).…”
Section: Climate and Maturitymentioning
confidence: 99%
“…They include simple heat units based on the accumulation of daily mean temperatures above a certain threshold temperature during growing period (Wiggans 1956, Brown 1960, Wang 1960, Baskerville & Emin 1969, Chen 1973. Others are: the sum of effective temperatures (Chirkov 1965, Gordeev et al 2006; effective degrees (Gilmore & Rogers 1958); the accumulated heat unit (Mederski et al 1973); growing degree units (Darby & Lauer 2002); P-days, which is a heat unit for the growth and development of potatoes (Sands et al 1979); corn heat units, used to define the relationship between temperature and the development of corn hybrids (Smith et al 1982, Bootsma 1994, Dwyer et al 1999, Bootsma et al 2004; the general thermal index, developed from statistically fitted maize development temperature response functions for the vegetative and grain-filling periods (Dwyer et al 1999); and photothermal units (McMaster & Smika 1988).There have been other approaches. One method calculates sums of positive temperatures over a period above a given threshold temperature (T base ), referred to as active temperatures for the growth period starting from the date of the onset of spring (e.g.…”
mentioning
confidence: 99%